Brazilian-Portuguese Linguistic Validation of the Velopharyngeal Insufficiency Effects on Life Outcome Instrument. Issue 8 (November 2019) - Denadai, Rafael; Raposo-Amaral, Cassio Eduardo; Sabbag, Anelise; Ribeiro, Rafael Andrade; Buzzo, Celso Luiz; Raposo-Amaral, Cesar Augusto; Hung, Man; Skirko, Jonathan R.
Abstract : Background: The purpose of this study was to conduct a linguistic validation of the velopharyngeal insufficiency (VPI) Effects on Life Outcome (VELO) instrument for use in Brazilian-Portuguese patients with VPI. Methods: The original English version of the VELO instrument was translated into Brazilian-Portuguese, back-translated, and adapted among the Brazilian patients (n = 21) with VPI and their parents, based on the standardized guidelines for the cross-culture adaption process. Discrepancies in the forward and backward translation steps were computed. Comprehension rates were captured for each debriefing interview. The content validity index (CVI) per item (I-CVI) and of the scale (S-CVI universal agreement [S-CVI/UA] and averaging [S-CVI/Ave]) were calculated. Results: Reconciliation of the 2 forward translations and the comparison between the back translation and the original VELO version resulted in some item wordings with discrepancies which were reviewed by the research team (translators, expert committee, and original developers of instrument). Three rounds of cognitive interviews also led to some revisions of wording. Comprehension rates of patients and their parents were 60% to 100%, 80% to 100%, and 100% in the first, second, and third rounds of cognitive interviews, respectively. The I-CVI, S-CVI/AU, and SCI/Ave for the Brazilian-Portuguese VELO version were 0.83 (or higher), 0.83 (or higher), and 0.97, respectively. Conclusions: The linguistic validation process of the VELO instrument created a cross-culturally equivalent Brazilian-Portuguese version for use in Brazilian-Portuguese speaking patients with VPI. Abstract : Supplemental Digital Content is available in the text